Mafhūm al-‘Adālat ‘inda Ibn Miskawaih wa Dauruhā fi Ri’āyat al-Bī’at - Nidzom, Muhammad Faqih; Kurnia Zainiati, Alifia (UIN Sunan Kalijaga Yogyakarta, 2022)
This article will discuss the concept of justice in Ibn Miskawaih's Ethics and the concept of the environmental conservation. The authors uses a descriptive-analytical method and a Sufi-philosophical approach in Ibn Miskawaih's work entitled Tahdzīb al-Akhlāq wa Tathhīr al-'Arāq. The results obtained by the author from this study are that justice, according to Ibnu Miskawaih, is the alignment of the architecture of the soul, behaviour, and human condition so that nothing exceeds or reduces one another. Ibn Miskawaih's justice lies in Islamic shari'ah as a measure of balance in a case and a way to achieve prosperity. Thus, the concept of justice has a significant role in environmental conservation and protection. It includes maintaining the balance of nature, which can be done by reforestation, normal earth development, maintaining health and cleanliness, and being able to direct in responding to the development of science and technology to achieve the welfare and maintain harmony between human beings and their environment.